<span>area is side by side.
so do 6.25*6.25 and that equals 39.0625
</span>
Answer:
x = -8 and x= 7
Step-by-step explanation:
recall that for a rational expression, the vertical asymptotes occur at x-values that causes the expression to become undefined. These occur when the denominator becomes zero.
Hence the asymptototes will occur in x-locations where the denominator , i.e
(x+8)(x-7) = 0
solving this, we get
(x+8) = 0 ----> x = -8
or
(x-7) = 0 ------> x = 7
hence the asymptotes occur x = -8 and x= 7
When you make the product of a binomial of the kind x + a times other binomial that is of the kind x - a, you obtain another binomial (not a trinomial), so any example with that form will be a counterexample that disproves the conjecture:
(x + a) * (x - a) = x^2 - a^2
For example, (x +3) * (x - 3) = x^2 - 9. So, not always the product of two binomials is a trinomial.
Answer:
DE
Step-by-step explanation:
6x + 5 = 4x + 5
2x + 5 = 5
2x = 0, x = 0
Y = 6(0) + 5, y = 5
Solution: x = 0, y = 5